An Analysis of Cultural Translation Strategies of Culinary Texts in The Complete Book of Pasta and Noodles from English to Indonesian - Resty Widya Kurniasari (Indonesian TESOL Journal, 2025)
This study investigates the translation strategies employed in translating cooking recipes from English into Indonesian, focusing on meaning fidelity, function, and readability. A total of 20 recipes were selected from The Complete Book of Pasta and Noodles and analyzed using Mona Baker’s (1992) and Peter Newmark’s (1988) translation strategy frameworks. The results show that the most dominant strategy was modulation (40%), followed by transposition (25%), cultural adaptation (20%), literal translation (10%), cultural substitution (5%), and borrowing (5%). These strategies indicate that translators must consider both linguistic and cultural differences to make recipes understandable and practical for Indonesian readers. This study aims to serve as a reference for culinary text translators in producing functional and effective translations.